2006
DOI: 10.1002/0471143030.cb2105s33
|View full text |Cite
|
Sign up to set email alerts
|

The Fluorescent Protein Color Palette

Abstract: Advances in fluorescent protein development over the past 10 years have led to fine‐tuning of the Aequorea victoria jellyfish color palette in the emission color range from blue to yellow, while a significant amount of progress has been achieved with reef coral species in the generation of monomeric fluorescent proteins emitting in the orange to far‐red spectral regions. It is not inconceivable that near‐infrared fluorescent proteins loom on the horizon. Expansion of the fluorescent protein family to include o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 158 publications
(289 reference statements)
0
40
0
Order By: Relevance
“…For many experimental applications, these oligomeric tendencies can be alleviated by mutagenesis of the dimer interface, at least when examined using biochemical techniques such as size-exclusion chromatography (26) and analytical ultracentrifugation (23). Although most of the FPs used in this study (mEGFP, mNeGr, mCit, tagRFPt, and mApple) were previously found to be monomeric in solution, the FPs may be prone to oligomerization artifacts when a high local concentration is generated by fusion to oligomeric proteins (24). For example, tagRFP and EGFP were susceptible to oligomerization when fused to the cytoplasmic face of a resident endoplasmic reticulum membrane protein (27).…”
Section: Discussionmentioning
confidence: 99%
“…For many experimental applications, these oligomeric tendencies can be alleviated by mutagenesis of the dimer interface, at least when examined using biochemical techniques such as size-exclusion chromatography (26) and analytical ultracentrifugation (23). Although most of the FPs used in this study (mEGFP, mNeGr, mCit, tagRFPt, and mApple) were previously found to be monomeric in solution, the FPs may be prone to oligomerization artifacts when a high local concentration is generated by fusion to oligomeric proteins (24). For example, tagRFP and EGFP were susceptible to oligomerization when fused to the cytoplasmic face of a resident endoplasmic reticulum membrane protein (27).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, for VLP-forming proteins, the tag must not interfere with the capacity of the viral protein or proteins to self-assemble. eGFP was therefore chosen as the fluorescent tag because of its enhanced fluorescent properties, photostability, and relatively small size, as well as the fact that it is a widely used research tool (45)(46)(47). For the eGFP-labeled VLPs described in this report, fluorescence was stable even after particle purification (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Before transfection, growth media was replaced by Optimem media without FBS (Gibco) and 8 µg of plasmid DNA (mCherry-Mito-7 was a gift from Michael Davidson (Addgene plasmid # 55102) [22] was transfected using 20 µL of lipofectamine reagent (Invitrogen, Carlsbad, CA, USA) per condition. After 5 h of transfection, the media was replaced by complete media.…”
Section: Mcherry-mito7 Stable Transfection In A549 Cellsmentioning
confidence: 99%